Internal and External Factors Affecting the Development of BUMdes Cadaskertajaya, Telagasari District, Karawang Regency, Indonesia - Sulandjari, Kuswarini; Azzahra, Fatimah; Muslimah, Tikka (KnE Social Sciences, 2024)
Village-owned businesses (BUMDes) play an essential role in the economic development of the village. The main objective of these businesses is to improve the village economy, reduce population migration to cities, and explore local economic potential. Despite these benefits, the development of BUMDes is often limited by internal factors, such as the lack of knowledge, attitude of members, dishonesty, and lack of transparency, as well as external factors, including limited access to information technology. Therefore, this study aims to identify the internal and external factors influencing BUMDes. Data were obtained through interviews with BUMDes administrators, heads of farmer groups, and heads of Gapoktan, as well as community representatives. The results show that internal weakness factors directly influenced the progress of these businesses, while internal strength factors had a limited positive impact.. External factors, such as village government assistance and the People's Business Credit (KUR), had an important role in supporting the development of businesses, however, certain limitations, including a lack of skills and knowledge, must be addressed. The results also suggest several strategic recommendations, such as increasing knowledge and skills through training, enhancing financial management and bookkeeping, and encouraging active community participation. These activities are expected to help BUMDes Cadaskertajaya become a model of success in empowering the village economy and improving the welfare of local communities. Keywords: inhibitory behavior, village development, bumdes cadaskertajaya